Fibrous monolithic ceramic with a single alumina phase: Fracture and high‐temperature tribological behaviors. Issue 8 (21st March 2019) - Su, Yunfeng; Fan, Hengzhong; Zhang, Yongsheng; Song, Junjie; Chen, Shuna; Hu, Litian
Abstract: Fabrication of fibrous monolithic ceramic with bamboo‐like structures is a promising method to improve the mechanical properties of ceramics through extrinsic reinforcement. Nevertheless, heterogeneous boundaries are easily oxidized at high temperatures, which seriously limits the long‐term use of these materials when employed in high‐temperature and high/low‐temperature alternating environments. In this study, a "plain" ceramic—a single‐component and complex‐structure Al2 O3 ceramic—was successfully designed and prepared using nano‐sized Al2 O3 as polycrystalline fibers and micro‐sized Al2 O3 as boundaries to obtain a structure with a fibrous monolithic architecture. Self‐toughening of Al2 O3 ceramics can be achieved by introducing hierarchical architectures derived from the difference between grain sizes of fibers and boundaries, which gives the ceramics high fracture toughness and reliability. Moreover, the material demonstrated a low friction coefficient and high wear‐resistance properties when coupled with C/C composites at room temperature, 800°C, and in the alternating temperature enviroment between room temperature and 800°C. Abstract : A single‐component and complex‐structure Al2 O3 fibrous monolithic ceramic was designed and prepared through regular difference in Al2 O3 grain sizes, in which nano‐sized and micro‐sized Al2 O3 were taken as polycrystalline fiber cells and cell boundaries, respectively. In this way the coarse‐grained boundaries can induce crack deflection and propagation along the boundaries to dissipate energy, which gives the ceramic high fracture toughness and reliability. Moreover, the fibrous monolithic ceramic with a single alumina phase will alleviate the oxidation of boundaries and exfoliation of fibers and boundaries. Thereby, this design will promote the application of these materials when employed in high‐temperature environment..